2009
DOI: 10.1159/000268107
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Home Visits in the Outpatient Treatment of Patients with Alcohol Dependence

Abstract: The purpose of this study was to compare the cost-effectiveness of conventional outpatient treatment for alcoholic patients (CT) with this same conventional treatment plus home visits (HV), a new proposal for intervention within the Brazilian outpatient treatment system. A cost-effectiveness evaluation alongside a 12-week randomized clinical trial was performed. We identified the resources utilized by each intervention, as well as the cost according to National Health System (SUS), Brazilian Medical Associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…While the overall number of deaths did not differ significantly between the two environments, the patients' and care givers' satisfaction was significantly higher in the "at-home-group" [21]. A recent study from Brazil has also demonstrated the cost effectiveness of home visits in the treatment of alcohol dependent patients [22]. These scientific observations would seem to suggest that home visits deliver an enhanced quality of care and can be cost effective for people suffering from chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…While the overall number of deaths did not differ significantly between the two environments, the patients' and care givers' satisfaction was significantly higher in the "at-home-group" [21]. A recent study from Brazil has also demonstrated the cost effectiveness of home visits in the treatment of alcohol dependent patients [22]. These scientific observations would seem to suggest that home visits deliver an enhanced quality of care and can be cost effective for people suffering from chronic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological interventions were the most common technology to be assessed, mainly in schizophrenia, alcohol/substance disorder, and major depressive disorders. [36][37][38][39][40] This scarcity shows the need for development of the mental health economics field in Brazil, mainly regarding human resources, to conduct methodologically adequate research.…”
Section: Health Technology Assessment (Hta) In Mental Health In Brazilmentioning
confidence: 99%
“…Of these studies, most were on schizophrenia (Leitão et al, 2006;Lindner et al, 2009;Daltio et al, 2011), one on alcohol addiction (Moraes et al, 2010) and one on the major depressive disorders (Machado et al, 2007). Two studies performed cost analyses (Leitão et al, 2006;Lindner et al, 2009) and three were full economic analyses (Daltio et al, 2011;Machado et al, 2007;Moraes et al, 2010). Most CE studies used secondary data collected from international literature.…”
Section: Health Economics In Mental Healthmentioning
confidence: 99%
“…Pharmacological interventions were the most common technology assessed (Leitão et al, 2006;Lindner et al, 2009;Daltio et al, 2011;Machado et al, 2007). One evaluation of health services and programs was also found (Moraes et al, 2010). In general, costs were evaluated under the perspective of the public healthcare system and prices were assessed as if they were purchased by the government for all studies (Leitão et al, 2006;Lindner et al, 2009;Daltio et al, 2011;Machado et al, 2007;Moraes et al, 2010).…”
Section: Health Economics In Mental Healthmentioning
confidence: 99%